2017
DOI: 10.12968/bjcn.2017.22.sup3.s41
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated wound healing with combined NPWT and IPC: a case series

Abstract: Negative pressure wound therapy (NPWT) and intermittent pneumatic compression (IPC) have traditionally been used in patients with chronic complicated non-healing wounds. The aim of this study (retrospective case series) was to describe the use of NPWT in combination with IPC in patients with a relatively short history (2-6 months) of ulcers. All wounds showed improved healing during the treatment period with marked or moderate reduction in ulcer size, and granulation tissue formation was markedly stimulated. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Similarly, the biological effects of long-term intermittent mechanical loading of the tissues need to be further investigated. Several studies have found beneficial effects of intermittent pneumatic compression on fracture and soft-tissue healing after trauma (Airaksinen, Kolari, & Miettinen, 1990;Arvesen, Nielsen, & Fogh, 2017;Khanna, Gougoulias, & Maffulli, 2008) due to upregulation of collagen type I synthesis (Abdul Alim, Domeij-Arverud, Nilsson, Edman, & Ackermann, 2018). However, the pressures used would appear to be considerably lower than those presumably required for joint stabilisation.…”
Section: Limitationsmentioning
confidence: 99%
“…Similarly, the biological effects of long-term intermittent mechanical loading of the tissues need to be further investigated. Several studies have found beneficial effects of intermittent pneumatic compression on fracture and soft-tissue healing after trauma (Airaksinen, Kolari, & Miettinen, 1990;Arvesen, Nielsen, & Fogh, 2017;Khanna, Gougoulias, & Maffulli, 2008) due to upregulation of collagen type I synthesis (Abdul Alim, Domeij-Arverud, Nilsson, Edman, & Ackermann, 2018). However, the pressures used would appear to be considerably lower than those presumably required for joint stabilisation.…”
Section: Limitationsmentioning
confidence: 99%
“…On the other hand, our results showed differences between groups in maximal and mean values > 0.7ºC immediately post-intervention and 24 h post-intervention in front and back lower limbs in which a differences in thermal image (>0.7ºC) can be associated with structural or physiological abnormalities that contribute to a decrease in the quadriceps power [25,39]. These differences >0.7ºC in the skin temperature between elite soccer players (INPT vs. ART) possibly by INPT contribute to the process of recovery from the increased blood flow in the microcirculation, reduction of edema, removal of exudate, cell proliferation and angiogenesis, which can lead to faster neuromuscular recovery, reduced muscle tension, and reduced pain sensation [6,15].…”
Section: Discussionmentioning
confidence: 99%
“…In comparison to other cases, we find our case unique because of the extension of the wounds and our management with negative pressure wound therapy. We followed the World Society of Emergency Surgery (WSES) Guidelines for Management of Skin and Soft Tissue Infections recommendations and even when negative pressure wound therapy is not part of the conventional recommendations, and according to other studies, its use is still controversial, we had positive outcomes with this approach in terms of wound healing and pain control [ 7 , [17] , [18] , [19] , [20] , [21] , [22] , [23] ].…”
Section: Discussionmentioning
confidence: 99%